Analysis of point deduction patterns in Taekwondo using association rule learning - Jeon, M. (International Journal of Performance Analysis in Sport, 2019)
Three hundred and forty five matches from the men`s division of the 2017 Muju International Taekwondo Competition were studied to record the instances and nature of point deductions. Deductions were noted in respect to match conditions, match times, positions in court, and the type of deductions. These data were used to record frequencies as well as correlation between events using association rule learning. Firstly, we found the highest frequency of point deductions occurred when an athlete already has lower scores during a match (i.e. when they are losing in the match). Deductions were most numerous during the second round, and when play was in centre-of-court. Point deductions of number 3 were the most common (grabbing or pushing the opponent). Secondly, correlation between point-deductions and certain events were found in the following order: 2 points (out-of-bounds) against a winning contestant in the third round fighting at the outskirts of the court; 4 points (miscellaneous) in the first round to drawn contestants fighting at the centre-of-court; 1 point (falling) against a losing contestant in the third round fighting at the centre-of-court.